Galindians Across the Vastness of Europe: Archaeology, History, Linguistics - Luchtanas, Aleksiejus; Poliakovas, Olegas (Lietuvos istorijos studijos, 2018)
[article in Lithuanian; only abstract and key words in English]The supposition that the Galindians could take part in the Migration Period are being accepted as the scientific truth in Lithuania and associated mainly with the name of the Russian scholar V. Toporov. Although traces of the Galindian migrations are not found, Toporov’s main concepts were completely adopted by E. Jovaisha in his books and school manuals. The article regards the history of this question and its argumentation. The main focus of the paper is the methodology used by V. Toporov, and a systemic examination of all relative facts. During 1977–1983, the scholar published two theses and three small articles, which were all devoted to the Galindians. Yet his handling of the subject was somewhat unexpected. Before that, in 1972, V. Toporov published two substantial works, devoted to the toponymy of the Moscow region: any traces of the Galindians were absent there. It is possible to state that all aspects of the Galindian problematics were adopted by V. Toporov from another substantial work, written by V. B. Vilinbachov and N. V. Engovatov (1963). In many aspects, it would later become a starting point of his crackpot ideas. Traditionally, scholars relate the Galindians to the archaeological Bogaczewo culture. Its remains are located in the vicinity of the Mazurian Lake District, where the West-Baltic tribe was placed by Ptolemy (c. 100– c. 170 AD) and Peter of Dusburg († after 1326). A mass migration of a small tribe is unbelievable due to its very restricted economic and human potential. In historical records, the name Galindians is absent except for the mentions above. The so-called Eastern Galindians (люди Голѧдь – the people Goliad’) are certainly mentioned in the Russian chronicles only once, on 1147. However, the word Голѧдь in this context possesses some other meaning, while the word people (люди) is never being used with any ethnonym. Attempts to establish a connection between the Moshchin culture with the Goliad’ on Protva of the Russian chronicles are also unacceptable. We can mark a significant chronological gap of about five centuries between them, and the absence of any obvious archaeological monuments of the Goliad’ at the beginning of the second millennium.The conceptions of the Galindians by V. Toporov are not homogeneous. The conclusions he came to contradict one another: in one article he postulates a Great Galindia from the Moscow region to the Prussian lands, in another – huge Galindian migrations over the whole of Europe. His declarations about the simultaneous Galindians migrations with the Visigoths, Vandals, Burgundians, Lombards, as well as their migration to the Moscow region are certainly improbable or even absurd. V. Toporov’s assumption of Galindians migration with the Visigoths was based purely on the presumption that there was a warrior named Galindo among the Goths. This assumption was found to be false, as studies of Gothic prosopography discovered that such a Gothic name was absent. The name Galindo appeared much later and originated in one Frankish region; moreover, G- in Galindo was a Vulgar Latin hypercorrection of the initial Germanic W-.Thus, the migration ideas of the Galindians by V. Toporov and his followers have no historic, archaeological or linguistic grounds. They are only based on the affluent and fantastic misinterpretations of the anthroponomical and toponymic forms, collected by him. In many respects these forms are completely different. They were taken from various languages; originate from various territories that are extremely distant from one another, and known from different times. They only partially and often very distantly resemble the ethnonym Galindian.
Keywords: Galindians, Western Balts, Germanic tribes, Celts, Migration Period, archaeology, history, linguistics, ethnogenesis